(Nl@SI kRAUN (B:s (NrOMAN (B/s - (N{OU(B, (NiRWINs 1913-1984; (NgERASIMOW(B, (Na(B.(Ne(B.s ((NbARNAUL (B:s (NaLT(B. (NKN(B. (NIZD(B-(NWO(B,s, 1990)
(NoN RWALSQ K USPEHU(B. (Nk USPEHU (B- (NL@BOJ CENOJ(B. (NoN PYTALSQ WSEJ SWOEJ VIZNX@ dokazatx(B. (NdOKAZATX (B- (N^TO(B? (NpRI^INY \TOGO LEVALI W GLUBOKOM DETSTWE(B. (Nw ^EM(B-(NTO(B, (N^TO ON UWIDEL MNOGO LET NAZAD(B. (Nw ^EM(B-(NTO(B, (N^TO IZMENILO EGO (B- (NRAZ I NAWSEGDA(B.s
Keywords: (NaMERIKANSKAQ LITERATURAs